2018
DOI: 10.1002/bkcs.11403
|View full text |Cite
|
Sign up to set email alerts
|

TDDFT and MS‐CASPT2 Study of the Excited States of Para‐Methoxymethylcinnamate

Abstract: The vertical and adiabatic excitation energies of the ππ*, ππ*′, and nπ* states of the trans and cis isomers of para‐methoxymethylcinnamate (p‐MMC) were calculated using time‐dependent density functional theory and multistate complete active space second‐order perturbation theory (MS‐CASPT2) with reasonably sized basis sets. The adiabatic excitation energies of the ππ* state of trans‐p‐MMC calculated by TD‐CAM‐B3LYP and MS‐CASPT2 are in excellent agreement with the experimental value. The nπ* state lies at a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…There have been evidence and arguments for two general pathways: excitation to dissociative electronic states that results in fast dissociation directly from those states, and excitation followed by deactivation to ground electronic states from which the dissipated energy is sufficient to cleave the peptide backbone. 4349 Both pathways may be operative in the present work. It is also interesting to note that the dichotomy between the fragmentation yield reflecting secondary structure and the observed charge state of the fragmenting monomers of SA, which were consistent with an asymmetric charge partitioning pathway, can be rationalized together in terms of a recent model proposed by Loo et al .…”
Section: Discussionmentioning
confidence: 80%
“…There have been evidence and arguments for two general pathways: excitation to dissociative electronic states that results in fast dissociation directly from those states, and excitation followed by deactivation to ground electronic states from which the dissipated energy is sufficient to cleave the peptide backbone. 4349 Both pathways may be operative in the present work. It is also interesting to note that the dichotomy between the fragmentation yield reflecting secondary structure and the observed charge state of the fragmenting monomers of SA, which were consistent with an asymmetric charge partitioning pathway, can be rationalized together in terms of a recent model proposed by Loo et al .…”
Section: Discussionmentioning
confidence: 80%
“…Cinnamates and hydroxycinnamates 18,19,22,23,27,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] are from the above point of view a class of compounds of particular interest. They are ubiquitously employed in plants and bacteria for UV-B protection, while hydroxycinnamates are at the same time also used in nature as potent antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…27,31 In this context, a number of theoretical studies have investigated with a variety of techniques, including high-level quantum chemical approaches (complete active space selfconsistent field (CASSCF) and multi-state complete active space 2nd-order perturbation (MS-CASPT2)), the photophysical and photochemical properties of several cinnamate derivatives and/or reduced models of OMC -namely molecular structures including only the cinnamate chromophore nucleus but not the long aliphatic chain. [32][33][34][35][36][37][38][39][40][41][42][43] For example, the trans-cis photoisomerization route of substituted methylcinnamates was recently explored via single-component artificial force-induced reaction (SC-AFIR) combined with timedependent density functional theory (TD-DFT), highlighting a marked influence of the phenyl substituents on the decay mechanism. 42 Other studies at the TD-DFT/CIS level suggested appreciable solvent and hydrogen-bond effects on the photoisomerization mechanisms, 28,29 which were then corroborated by CASSCF and MS-CASPT2 calculations.…”
Section: Introductionmentioning
confidence: 99%